Optimal operation of park-level integrated energy system based on multi-agent cooperative game - Xu, Kaiwen; Liu, Zeyu; Sun, Weichen (Frontiers in Energy Research, 2022)
As the effects of climate change and environmental pollution become more serious, the requirements of low carbon emission are put forward to the operation of integrated energy systems. Under this trend, a cooperative-game-based operation optimization model for integrated energy systems is proposed in this paper. This model can achieve the multi-agent allocation and coordinate the operating costs and carbon emissions. The Anderson-accelerated-based alternating direction multiplication (AA-ADMM) method is used to improve the efficiency of solving the proposed model. Thereafter, the benefit of each agent is allocated by the Shapley value. Results indicate that the proposed model can provide a reasonable trade-off between operating costs and carbon emissions, and the proposed benefit allocation strategy is effective.